Fecal Dysbiosis and Immune Dysfunction in Chinese Elderly Patients With Schizophrenia: An Observational Study - Ling, Zongxin; Jin, Guolin; Yan, Xiumei; Cheng, Yiwen; Shao, Li; Song, Qinghai; Liu, Xia; Zhao, Longyou (Frontiers in Cellular and Infection Microbiology, 2022)
Schizophrenia (SZ) is a severe neuropsychiatric disorder with largely unknown etiology and pathogenesis. Mounting preclinical and clinical evidence suggests that the gut microbiome is a vital player in SZ. However, the gut microbiota characteristics and its host response in elderly SZ patients are still not well understood. A total of 161 samples was collected, including 90 samples from elderly SZ patients and 71 samples from healthy controls. We explored the gut microbiota profiles targeting the V3–V4 region of the 16S rRNA gene by MiSeq sequencing, and to analyze their associations with host immune response. Our data found that bacterial β-diversity analyses could divide the SZ patients and healthy controls into two different clusters. The Linear discriminant analysis Effect Size (LEfSe) identified the compositional changes in SZ-associated bacteria, including Faecalibacterium, Roseburia, Actinomyces, Butyricicoccus, Prevotella and so on. In addition, the levels of pro-inflammatory cytokines such as IL-1β were greatly increased in SZ patients while the levels of anti-inflammatory cytokines such as IFN-γ were markedly decreased. Correlation analysis suggested that these bacteria contributed to immune disturbances in the host that could be used as non-invasive biomarkers to distinguish the SZ patients from healthy controls. Moreover, several predicted functional modules, including increased lipopolysaccharide biosynthesis, folate biosynthesis, lipoic acid metabolism, and decreased bile acid biosynthesis, fatty acid biosynthesis in SZ-associated microbiota, could be utilized by the bacteria to produce immunomodulatory metabolites. This study, for the first time, demonstrated the structural and functional dysbiosis of the fecal microbiota in Chinese elderly SZ patients, suggesting the potential for using gut key functional bacteria for the early, non-invasive diagnosis of SZ, personalized treatment, and the development of tailor-made probiotics designed for Chinese elderly SZ patients.